Economic analysis and adaptation measures of small scale aquaculture in Roxas City, Capiz. - Baes, Marla May A. (2015.)
This research was conducted to find out the contribution of the aquaculture industry to the city and to the small-scale farmers of Roxas City. It also determined the socio-economic impacts brought by the hydrometeorological events and identified the adaptation measures employed by the local government and the aquaculture operators. This study used cost and return analysis, market based approaches and OLS regression to analyze the data gathered from the 187 small-scale milkfish, mussel, and oyster farmers in Roxas City. The findings showed that the aquaculture industry significantly contributed to revenue, employment, production and profit. However, the industry was affected by hydrometeorological events which brough about significant damage cost. Most of the aquaculture operators employed various adaptation strategies to cope with the hydro-meteorological occurrences. Some of them, however, did not find it necessary to adapt because either they do not have enough money to finance adaptation strategies of they perceive that the impacts are not that significant. This study recommends that the government should provide other alternative climate-resilientlivelihoods to the small-scale operators. It should also employ sustainable adaptation measures aside from providing trainings and seminars abput aquaculture operation such as by integrating climate change adaptation to aquaculture farming.
Research Paper (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Aquaculture Industry -- Roxas City